P1-S6.32 Optimising clinical systems to increase HIV/STI testing in gay men: the eTEST project. (10th July 2011) - Drummond, F; Lewis, L; Bourne, C; Ramanathan, V; Hocking, J; Wand, H; Donovan, B; Kaldor, J; Guy, R
Abstract : Background: Despite HIV/STI testing rates being high (∼60%) on an annual basis in gay men in Australia, the proportion of "high risk" gay men having two or more HIV/STI tests per year, as specified in clinical guidelines, appears quite low (20%). Mathematical modelling predicts that increasing the frequency of HIV/STI testing among gay men with high numbers of sexual partners to 3–6 monthly would effectively stop the HIV and syphilis epidemics over a ten year period. We developed a multi-faceted intervention package based on information technology which aims to increase STI/HIV testing in high-risk men gay men. We describe the process and outcomes of the development stage of the intervention. Methods: The intervention will be conducted over 2 years at 10–15 general practice clinics which see a high case load of gay men. These clinics provide both general healthcare and specialist sexual health and HIV management. All of these clinics utilise different patient management systems. We engaged a software company to develop a program adaptable to multiple clinic systems which aims to increase clinic efficiency and enhance sexual health testing. The process was undertaken over 12-month period in 2010 and involved extensive consultation with clinicians, stakeholders and information technology specialists. Results: The program has now been developed and has four key elements: (i) passive prompts to remind clinicians when the next HIV/STI test is due based on the patient's risk assessment profile, testing guidelines and clinic record of past testing; (ii) SMS-based recalls which are automatically sent to patients when HIV/STI testing is overdue; (iii) a sexual health resource tool bar on the computer desktop of primary care providers to provide partner notification websites, up-to-date education brochures and referral systems that support collaboration between providers; and (iv) a reporting enhancement which allows practice staff to look at their data for the achievement of best practice and data quality targets. Further details of the system and functionality will be provided in the poster. Conclusion: The program is the first clinical intervention we are aware of that addresses a range of important barriers to HIV/STI testing in a single information technology program. The system is currently being rolled out into the 10–15 clinics in Sydney and the impact of this intervention will be assessed by measuring the change in HIV/STI testing rates before-and-after the program. Interviews will also be conducted with clinicians and practice managers before and after the intervention to assess barriers to testing and acceptability and transferability of the intervention.